Empowerment of prison-assisted citizens (WBP) as craftsmen of basic plastic waste materials bags in class II Medan correctional facilities for women - Tarigan, Lita; Hiswani (Talenta Publisher, 2019)
Garbage in plastic form is quite difficult to decipher. Research shows that plastic waste will decompose within a period of 50 million years. However, this garbage can be processed into various kinds of creativity that have high selling points. Penitentiary Class IIA Tanjung Gusta Medan WBP numbered 98 people specifically women. According to information from Lapas officers that WBP needs skills to fill their free time, one of the important skills is to see the amount of plastic beverage waste so it is necessary to process the waste into various bags that have value. For this reason, community service is carried out to empower WBP in producing plastic beverage waste into various bags. The method of approach taken in devotion to WBP specifically for women is the method of lectures, discussions and demonstrations as well as conducting training, guidance and assistance to WBP. The Dedication Team has conducted socialization on the making of bags made from plastic beverage lining at WBP which aims to form an attitude and desire to be involved in these activities. Furthermore, training to increase knowledge and skills in WBP in processing and producing waste plastic beverage waste into various bags. Through increasing knowledge and skills, it is expected that high selling points will be obtained in the community and marketing will be assisted by cooperatives in remote areas. Based on this, the WBP empowerment activities specifically for women in making bags made from plastic beverage waste can increase their knowledge and skills in making various bags.